Analysis of the efficiency factors of electrotransformation of Bacillus subtilis to inactivate the aroK gene by the method of homologous recombination - Yui Chao; Lahodzich, Aleksei V. (Experimental Biology and Biotechnology, 2021)
A hyper-osmotic electrotransformation method was developed for strain Bacillus subtilis. Sorbitol and mannitol are included in the hyper-osmotic electroporation medium and recovery medium. In this study, the hyper-osmotic electroporation method was optimised to increase the transformation efficiency of B. subtilis strain 5434 (non-transformable by chemical methods) by 430 fold, with a maximum value of 8.6 ⋅ 105 CFU/µg of integrative plasmid DNA. With the electroporation setted 25 µF, 23 kV/cm, 200 Ω, the method was optimised as follows: a) the OD600 value of the bacterial culture solution was increased to about 1.2, which significantly enhanced survival of bacteria and quantity of viable B.subtilis strain 5434 cells after electroporation; b) the elution frequency of washing solution (hyper-osmotic electroporation medium) for complement cells was increased from 3 to 5 times, resulted in significantly reducing the conductivity of the hyper-osmotic electoporation medium with competent cells (electrocompetent cultue), and effectively extending the pulse time under the same electric field strength; c) quantity of integrative plasmid DNA added to hyper-osmotic electrocompetent culture was optimised. These results indicate that increasing the number of viable B. subtilis strain 5434 cells and reducing the number of metal ions in the electroporation solution mix (integrative plasmid DNA, competent cells of B. subtilis strain 5434, electroporation medium) are useful approach to improve transfomation efficiency of B. subtilis strain 5434. Concentration of shikimic acid in the fermentation medium was quantified by high performance liquid chromatography. Quantification of shikimic acid revealed that B. subtilis strain 5434p4SA produced 403.98 ± 9.1 µg/mL of shikimic acid.
Keywords: Bacillus subtilis; homologous recombination; hyper-osmotic electrotransformation; shikimate